General structures of control area cooperation for variable renewable energy integration in electric power systems - Tan, Chao; Teng, Xianliang; Zhang, Xiaobai; Pang, Tao; Cao, Rongzhang (Frontiers in Energy Research, 2024)
To integrate large-scale variable renewable energy resources (RESs) in modern power grids, coordinating control area (CA) operation is the most cost-effective method. This paper reviews the technical aspects of CA cooperation. Firstly, a brief overview of active balancing control within each CA is discussed. Secondly, the three general control structures for CA cooperation are innovatively proposed, corresponding implementation details are analyzed, and some representative technologies are also provided in systematic analysis. Then, some future research directions such as larger-scale power sharing by DC, active power control of RES bases, and the new structure for distributed energy resources in local power grids, are prospected. Finally, the changes in power systems brought about by the evolution and their importance for further promoting cooperation between CAs are summarized.